(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Efficient shallow drainage is crucial for sustaining agricultural productivity in limited-water irrigated areas, where water scarcity and soil degradation pose significant challenges. Conventional drainage designs often fail to account for the complex interactions among hydrological, geotechnical, and mechanical processes, leading to suboptimal performance. This study presents an integrated hydro‑geo‑mechanical assessment and technology framework for optimizing shallow drainage systems. The proposed approach combines field investigations, soil and water property analyses, and modeling of coupled hydro‑mechanical processes to evaluate drainage efficiency and soil stability under water-limited conditions. Results demonstrate that the integrated framework improves water distribution, reduces waterlogging risks, and enhances irrigation efficiency compared to conventional methods. The findings provide both a scientific basis and practical guidelines for implementing optimized shallow drainage systems in water-scarce agricultural regions.